A method for preparing tempered architectural ceramics based on dual-mechanism prestress synergistic strengthening

CN122167144BActive Publication Date: 2026-10-16MONALISA GRP CO LTD
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202610637620.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-11
Publication Date
2026-10-16
Estimated Expiration
2046-05-11

AI Technical Summary

Technical Problem

涂层法是利用了预应力层和坯体的热失配在建筑陶瓷表面引入残余压应力,为提升预应力强化效果,需要制得热膨胀系数较低的陶瓷表层,通常需要在陶瓷表层中引入锂辉石、透锂长石、锂熔块、硼熔块等原料,这就导致预应力建筑陶瓷的制造成本增大;且低膨胀组分的引入会对建筑陶瓷烧成温度产生较大的影响,继而会增加钢化建筑陶瓷的工业制造难度

Benefits of technology

(1)本发明通过调控内坯层与外坯层的化学组分,改变其物相组成:内坯层为高硅长石质瓷(钾钠质瓷),其以非晶玻璃相为主,结晶相组成以石英和莫来石为主;外坯层为钙镁质瓷,其以结晶相为主,且结晶相组成以钙长石和透辉石为主。一方面,利用物相组成差异,可调控内坯层与外坯层的热膨胀系数(钙长石和透辉石的热膨胀系数低于石英和硅酸盐玻璃),继而可利用热膨胀系数失配而在建筑陶瓷表面引入残余压应力;另一方面,由于内坯层中含有一定量的石英结晶相,其在降温过程中会发生相变(β-石英转变为α-石英),且伴随着体积收缩,由此产生的收缩应变可在建筑陶瓷表面引入残余压应力。继而,利用热膨胀系数失配与石英相变收缩可强化建筑陶瓷的预应力增强效果,并大幅度提升建筑陶瓷的弯曲强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122167144B_ABST
    Figure CN122167144B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of mechanical strengthening of building ceramics, and relates to a tempered building ceramic preparation method based on double-mechanism prestress synergistic strengthening. The preparation method comprises the following steps: preparing an inner green layer ceramic powder into an inner green layer ceramic body; applying an outer green layer ceramic slurry on the surface and bottom surface of the inner green layer ceramic body to form an outer green layer-inner green layer-outer green layer laminated ceramic body; applying a surface glaze on the surface of the outer green layer-inner green layer-outer green layer laminated ceramic body, jet printing a normal ink pattern, and applying a protective glaze, and then performing sintering to obtain the tempered building ceramic based on double-mechanism prestress synergistic strengthening. Through chemical composition design of the inner green layer and the outer green layer, the present application can introduce residual compressive stress on the surface of the building ceramic by comprehensively utilizing quartz phase change and thermal expansion coefficient difference under the building ceramic manufacturing conditions, and then realize efficient tempering of the building ceramic, thereby effectively improving the bending strength of the building ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of mechanical strengthening technology of building ceramics, and relates to a method for preparing tempered building ceramics based on dual-mechanism prestressed synergistic strengthening. Background Technology

[0002] For brittle materials like ceramics, their compressive strength is much higher than their tensile strength, and most cracking and failure originate on the ceramic surface. Therefore, by introducing residual compressive stress into the ceramic surface layer, surface crack propagation can be suppressed and some of the tensile stress during load-bearing can be offset, thereby improving its flexural strength and achieving the purpose of prestressing strengthening. This residual stress (also known as prestressing) strengthening method is flexible in design and is a simple and effective strengthening method, which has attracted widespread attention from researchers both domestically and internationally.

[0003] Given the high design flexibility of prestressed strengthening, a series of prestressed strengthened building ceramics (tempered building ceramics) have been developed in recent years. Chinese patents CN113264783B (application number 202110815918.1), CN112047757A (application number 202010941618.3), CN110723988B (application number 201911067479.X), CN109336556B (application number 201811371056.2), and CN121426539A (application number 202511986171.0) all employ a coating method, applying a low-expansion coating (base glaze, prestress layer) to both sides of the building ceramic body. This utilizes thermal mismatch to create residual compressive stress on the surface of the building ceramic, achieving tempering and strengthening. Chinese patent CN112047721A (application number 202010940467.X) prepares low-shrinkage layer-green body-low-shrinkage layer laminated building ceramics through a dry pressing lamination method. It utilizes thermal mismatch to introduce residual compressive stress on the surface of the green body, thereby improving the mechanical strength of the building ceramics. Essentially, it still belongs to the coating method, only the coating preparation process has been changed. Chinese patents CN109704721B (application number 201910108796.5) and CN109608181A (application number 201910109507.3), etc., borrow from the technical solution of tempered glass ion tempering, using K in molten salt... + Na inside the tile + Ion exchange is performed because K + Radius greater than Na +After chemical replacement, the ions on the glass surface occupy more space, resulting in a "clogging" phenomenon and causing the surface volume to expand, thus forming a compression prestressed layer to improve the mechanical strength of building ceramic tiles. Chinese patent CN116462495B (application number 202310464079.2) combines coating and ion tempering methods, utilizing the introduction of a low-expansion coating and ion exchange treatment with alkali metal molten salt to achieve dual prestressing strengthening of building ceramics.

[0004] Based on the uniform strain model of materials mechanics, it is known that the residual stress on the surface of laminated ceramic samples is positively correlated with the difference in thermal expansion coefficients between the surface and core layers. Therefore, to improve the prestressing strengthening effect, the residual compressive stress on the surface needs to be increased, which means increasing the difference in thermal expansion coefficients between the surface and core layers. The coating method utilizes the thermal mismatch between the prestressing layer and the green body to introduce residual compressive stress on the surface of building ceramics. To improve the prestressing strengthening effect, a ceramic surface layer with a low thermal expansion coefficient is required. This typically involves introducing raw materials such as spodumene, petalite, lithium frit, and boron frit into the ceramic surface layer, which increases the manufacturing cost of prestressed building ceramics. Furthermore, the introduction of low-expansion components significantly affects the firing temperature of building ceramics, thereby increasing the industrial manufacturing difficulty of tempered building ceramics. The ion exchange method requires prolonged high-temperature treatment with molten salt and is affected by the chemical composition of the material (Na...). + The high content and good strengthening effect, production cost (nitrate molten salt is expensive, flammable and explosive), production cycle (the firing cycle of building ceramics is 40~60 min, and the optimal time for ion exchange is several hours) and the thermal shock damage to the ceramic surface during molten salt treatment make it difficult for this technology to be applied in the field of large-scale manufacturing of building ceramics. Summary of the Invention

[0005] Currently, the coating method mainly utilizes the difference in thermal expansion coefficients between the base glaze and the ceramic body to introduce thermal mismatch during the cooling process after firing. This leads to residual compressive stress on the surface of the building ceramic, thereby achieving the technical effect of prestressing enhancement. The chemical composition and thermal expansion coefficient of the building ceramic body change relatively little. To improve the prestressing strengthening effect, the common approach is to reduce the thermal expansion coefficient of the base glaze (prestressing layer). However, to achieve co-firing of the base glaze and the body, and to usually consider the lower manufacturing cost of the base glaze (both boron and lithium raw materials are relatively expensive), the adjustment range of the base glaze's thermal expansion coefficient is also relatively limited. Consequently, further improving the prestressing strengthening effect presents certain technical challenges.

[0006] In view of this, the present invention develops a method for preparing tempered building ceramics based on dual-mechanism prestressed synergistic reinforcement. By designing the chemical composition of the inner core blank layer (inner blank layer) and the bottom slurry prestressed ceramic layer (outer blank layer), the present invention can comprehensively utilize the difference in quartz phase transformation and thermal expansion coefficient to introduce residual compressive stress in the bottom slurry ceramic layer under the conditions of building ceramic manufacturing, thereby achieving efficient tempering of the building ceramics and effectively improving their flexural strength.

[0007] The preparation method of tempered building ceramics based on dual-mechanism prestressed synergistic reinforcement includes the following steps: Step 1: Prepare the inner layer ceramic powder into an inner layer ceramic body; the inner layer ceramic is a high-silica feldspar ceramic, and its phase after firing is mainly amorphous glass phase, with crystalline phase containing quartz and mullite as auxiliary phase. Step 2: Apply outer layer ceramic slurry to both the surface and bottom of the inner layer ceramic body to form an outer-inner-outer layer composite ceramic body; the outer layer ceramic is a calcium-magnesium porcelain, and its phase after firing is mainly a crystalline phase containing calcium feldspar and diopside, with an amorphous glass phase as the auxiliary phase. Step 3: Apply a surface glaze to the surface of the laminated ceramic body consisting of an outer blank, an inner blank, and an outer blank; Step 4: Print a pattern using ordinary ink on the surface of the laminated ceramic body (outer blank-inner blank-outer blank) after applying the surface glaze. Step 5: Apply a protective glaze to the surface of the laminated ceramic body consisting of an outer blank, an inner blank, and an outer blank after inkjet printing of a pattern using ordinary ink. Step 6: Fire the laminated ceramic body with outer blank-inner blank-outer blank after applying protective glaze to obtain tempered building ceramics based on dual-mechanism prestress synergistic strengthening.

[0008] In an optional embodiment, the chemical composition of the inner ceramic layer includes, by mass percentage: SiO2 66%~78%; Al2O3 14%~21%; Fe2O3 0.3%~0.6%; TiO2 0~0.1%; CaO 0.1%~0.3%; MgO 0.7%~2.0%; K2O 2.0%~3.7%; Na2O 1.8%~3.5%; and loss on ignition 2%~6%.

[0009] In an optional embodiment, the mineral composition of the inner ceramic layer includes, by mass percentage: 18%~35% sodium feldspar; 23%~41% potassium feldspar; 10%~30% clay; 2%~5% bentonite; 2%~6% calcined talc; and 5%~25% quartz.

[0010] In an optional embodiment, the chemical composition of the outer ceramic layer includes, by mass percentage: SiO2 45%~50%; Al2O3 13%~16%; Fe2O3 0.3%~0.6%; TiO2 0%~0.5%; CaO 17%~25%; MgO 6.7%~8.6%; K2O 1.0%~1.9%; Na2O 0.6%~1.5%; P2O5 0.8%~2.5%; and loss on ignition 3%~7%.

[0011] In an optional embodiment, the mineral composition of the outer ceramic layer includes, by mass percentage: 4%~10% sodium feldspar; 10%~20% potassium feldspar; 10%~25% clay; 2%~5% bentonite; 20%~35% diopside; 20%~40% mineral powder; and 2%~6% tricalcium phosphate.

[0012] In an optional embodiment, the specific gravity of the ceramic slurry in the outer green layer is 1.55~1.70 g / cm³. 3 The application rate of ceramic slurry on one side of the outer layer is 800~1800 g / m. 2 .

[0013] In an optional embodiment, the coefficient of thermal expansion of the inner ceramic layer is greater than that of the outer ceramic layer; the coefficient of thermal expansion of the inner ceramic layer is 7.8 × 10⁻⁶ in the range of room temperature to 600 °C. -6 ~9.0×10 -6 K -1 The coefficient of thermal expansion of the outer ceramic layer is 6.5 × 10⁻⁶ in the range of room temperature to 600 °C. -6 ~7.2×10 -6 K -1 .

[0014] In an optional embodiment, the crystalline phase of the outer ceramic layer has a nanocrystalline structure, and the porosity of the outer ceramic layer is higher than that of the inner ceramic layer. For example, the porosity of the inner ceramic layer is 3% to 5%, while that of the outer ceramic layer is 15% to 20%.

[0015] In an optional embodiment, the chemical composition of the glaze includes, by mass percentage: SiO2 53%~60%; Al2O3 25%~30%; Fe2O3 0.2%~0.5%; TiO2 0.1%~0.2%; CaO 0.2%~0.8%; MgO 0.1%~0.5%; K2O 2%~6%; Na2O 2%~3.5%; ZrO2 4%~8%; and loss on ignition 2%~5%.

[0016] In an optional embodiment, the glaze is applied by spraying or pouring; the specific gravity of the glaze is 1.40~1.45 g / cm³. 3The glaze application rate is 500~650 g / m². 2 .

[0017] In an optional embodiment, the chemical composition of the protective glaze includes, by mass percentage: SiO2 43%~48%; Al2O3 15%~19%; Fe2O3 0~0.2%; TiO2 0~0.2%; CaO 5%~12%; MgO 3.3%~4.5%; K2O 0.8%~2.7%; Na2O 3.3%~4.6%; ZnO 1.1%~3.8%; BaO 0.6%~7.8%; SrO 0~2%; and loss on ignition 9%~11%.

[0018] In an optional embodiment, the protective glaze is applied by spraying or pouring; the specific gravity of the protective glaze is 1.30~1.45 g / cm³. 3 The glaze application rate is 400~800 g / m². 2 .

[0019] In an optional embodiment, the maximum firing temperature is 1130~1160 ℃, and the high-temperature holding time is 15~30 min.

[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention modifies the phase composition of the inner and outer blank layers by adjusting their chemical composition: the inner blank layer is a high-silica feldspar porcelain (potassium-sodium porcelain), which is mainly composed of amorphous glass phase and quartz and mullite as the main crystalline phases; the outer blank layer is a calcium-magnesium porcelain, which is mainly composed of crystalline phases, with anorthite and diopside as the main crystalline phases. On the one hand, by utilizing the difference in phase composition, the thermal expansion coefficients of the inner and outer blank layers can be controlled (the thermal expansion coefficients of anorthite and diopside are lower than those of quartz and silicate glass), and then residual compressive stress can be introduced on the surface of the building ceramic by utilizing the mismatch in thermal expansion coefficients; on the other hand, since the inner blank layer contains a certain amount of quartz crystalline phase, it will undergo a phase transformation (β-quartz transforms into α-quartz) during the cooling process, accompanied by volume shrinkage, and the resulting shrinkage strain can introduce residual compressive stress on the surface of the building ceramic. Subsequently, the prestressing enhancement effect of the building ceramic can be strengthened by utilizing the mismatch in thermal expansion coefficients and the shrinkage of quartz phase transformation, and the bending strength of the building ceramic can be greatly improved.

[0021] (2) The outer blank layer of this invention has the characteristics of being lightweight and high-strength, which can significantly improve the machinability of tempered building ceramics. The crystalline phase content of the outer blank layer is as high as 90wt%, and the crystalline phase has a typical nano-micro (crystalline) structure, which makes it still have high mechanical strength under the premise of high porosity. Under normal circumstances, although tempering can effectively improve the bending strength of ceramics or glass, it will reduce the machinability of ceramics or glass. Because machining will destroy the surface compressive stress layer, the internal tensile stress will be released instantly without restraint, resulting in the overall breakage of tempered ceramics or glass. This invention utilizes the porosity of the outer blank layer to effectively inhibit the crack propagation of tempered building ceramics during machining and reduce the processing stress, thereby making it less likely for tempered building ceramics to suffer sudden damage caused by crack instability and propagation during cutting and grinding, effectively improving its machinability.

[0022] (3) Based on the actual manufacturing conditions of building ceramics, the present invention has developed an outer blank layer-inner blank layer-outer blank layer-glaze-protective glaze composite structure, that is, an outer blank layer is evenly set on both sides of the inner blank layer, which is not only conducive to the realization of the prestress strengthening effect of building ceramics, but also can significantly improve the brick shape of tempered building ceramics and increase the yield. Attached Figure Description

[0023] Figure 1 This is a schematic diagram of the cross-sectional structure of building ceramics based on dual-mechanism prestressed synergistic reinforcement. 1—Outer body layer; 2—Inner body layer; 3—Surface glaze; 4—Protective glaze.

[0024] Figure 2 This is the XRD pattern of the inner blank layer of Example 1.

[0025] Figure 3 This is the XRD pattern of the outer blank layer in Example 1.

[0026] Figure 4 This is a graph showing the correlation between the coefficient of thermal expansion of the inner and outer ceramic layers and temperature in Example 1.

[0027] Figure 5 These are SEM images of the outer and inner body layers of the tempered building ceramics in Example 1 (left image) and the inner body layer, outer body layer, and glaze interface (right image). 1—Outer body layer; 2—Inner body layer; 3—Glaze.

[0028] Figure 6 This is a SEM image of the outer ceramic layer of Example 1.

[0029] Figure 7 The images show the indentation morphology of the outer ceramic layers in Example 1 and Comparative Example 2. (a) The outer ceramic layer in Comparative Example 2; (b) The outer ceramic layer in Example 1. Detailed Implementation

[0030] In order to improve the prestressing strengthening effect of tempered building ceramics, this invention proposes a method for preparing tempered building ceramics based on dual-mechanism prestressing synergistic strengthening.

[0031] Tempered architectural ceramics based on dual-mechanism prestressed synergistic reinforcement possess a laminated structure of outer body layer - inner body layer - outer body layer - surface glaze layer - protective glaze layer, and its cross-sectional structure is as follows: Figure 1 As shown, the outer body layer is symmetrically arranged on the surface and bottom surface of the inner body layer, and the surface glaze layer is arranged on the surface of the ceramic body composed of the outer body-inner body-outer body layer. The surface refers to the direction facing the decorative surface (protective glaze). The bottom surface refers to the direction away from the decorative surface. The inkjet pattern layer is located between the surface glaze layer and the protective glaze layer, and serves only as partial decoration.

[0032] The following example illustrates a method for preparing tempered building ceramics based on dual-mechanism prestressed synergistic reinforcement.

[0033] Prepare inner-layer ceramic powder to form an inner-layer ceramic green body. The forming method is unrestricted; dry pressing can be used.

[0034] The inner ceramic body is a high-silica feldspar ceramic, and its chemical composition includes, by mass percentage: SiO2 66%~78%; Al2O3 14%~21%; Fe2O3 0.3%~0.6%; TiO2 0~0.1%; CaO 0.1%~0.3%; MgO 0.7%~2.0%; K2O 2.0%~3.7%; Na2O 1.8%~3.5%; and loss on ignition 2%~6%. In an optional embodiment, the chemical composition of the inner ceramic layer includes, by mass percentage: SiO2 66%~78%; Al2O3 14%~21%; Fe2O3 0.3%~0.6%; TiO2 0.01%~0.1%; CaO 0.1%~0.3%; MgO 0.7%~2.0%; K2O 2.0%~3.7%; Na2O 1.8%~3.5%; and loss on ignition 2%~6%.

[0035] As a preferred option, the mineral composition of the inner ceramic layer includes, by mass percentage: 18%~35% sodium feldspar; 23%~41% potassium feldspar; 10%~30% clay; 2%~5% bentonite; 2%~6% calcined talc; and 5%~25% quartz.

[0036] Weigh and ball-mill the raw materials according to the proportion of the inner layer ceramic until the median particle size of the ceramic powder reaches 8~12 μm. Then, remove iron and spray granulate to obtain the inner layer ceramic powder.

[0037] It is worth noting that the inner-body ceramic of this invention is a high-silica feldspar ceramic, which requires residual quartz crystal phase after firing (the crystalline phase composition is mainly quartz and mullite). The shrinkage caused by the quartz phase transformation (β-quartz to α-quartz) during the cooling process can then introduce residual compressive stress into the ceramic surface. The flux used in the inner-body ceramic is K2O, Na2O, and a small amount of MgO, mainly to avoid the high-temperature melting of SiO2 by alkaline earth metal oxides, thus facilitating the formation of the residual quartz crystal phase. Therefore, the inner-body ceramic is a high-silica feldspar ceramic, and its phase after firing is mainly an amorphous glassy phase, with crystalline phases containing quartz and mullite as auxiliary phases. In optional embodiments, the mass content of the amorphous glassy phase in the inner-body ceramic is >50wt%, the mass content of the quartz phase is 10%~30%, and the mass content of the mullite phase is 10%~20%.

[0038] The MgO content is 0.7%~2.0%, and it is mainly used in conjunction with K2O and Na2O fluxes to reduce the firing temperature of the inner ceramic layer by utilizing their mixed alkali effect. If the MgO content is too low, the firing temperature of the inner ceramic layer will be too high; if the MgO content is too high, it will intensify the high-temperature melting of SiO2 by MgO, which is not conducive to the formation of residual quartz crystal phase.

[0039] The SiO2 content is 66%~78%. If the SiO2 content is too low, it will not be conducive to the formation of residual quartz crystal phase; if the SiO2 content is too high, it will affect the thermal stability of the inner layer ceramic body and make the ceramic body prone to cracking and damage during heating.

[0040] The quartz raw material is high-purity quartz with an average particle size of 23 ~ 43 μm (325 ~ 600 mesh). If the particle size is too small, the quartz particles will easily melt into the glass phase during high-temperature firing, resulting in a low content of residual quartz crystal phase. If the particle size is too large, it will reduce the thermal stability of the inner layer ceramic body and make it easy for the ceramic body to crack and break during heating.

[0041] Prepare an outer layer ceramic slurry and apply it to the symmetrical surfaces (i.e., the surface and bottom) on both sides of the inner layer blank.

[0042] The outer ceramic body is a calcium-magnesium ceramic, and its chemical composition includes, by mass percentage: SiO2 45%~50%; Al2O3 13%~16%; Fe2O3 0.3%~0.6%; TiO2 0~0.5%; CaO 17%~25%; MgO 6.7%~8.6%; K2O 1.0%~1.9%; Na2O 0.6%~1.5%; P2O5 0.8%~2.5%; and loss on ignition 3%~7%. In an optional embodiment, the chemical composition of the outer ceramic layer includes, by mass percentage: SiO2 45%~50%; Al2O3 13%~16%; Fe2O3 0.3%~0.6%; TiO2 0.01%~0.5%; CaO 17%~25%; MgO 6.7%~8.6%; K2O 1.0%~1.9%; Na2O 0.6%~1.5%; P2O5 0.8%~2.5%; and loss on ignition 3%~7%.

[0043] As a preferred option, the mineral composition of the inner ceramic layer includes, by mass percentage: 4%~10% sodium feldspar; 10%~20% potassium feldspar; 10%~25% clay; 2%~5% bentonite; 20%~35% diopside; 20%~40% mineral powder; and 2%~6% tricalcium phosphate.

[0044] In an optional embodiment, the ore powder is blast furnace slag powder, and its chemical composition contains a CaO content of not less than 30% by mass. As an example, the chemical composition of the ore powder includes, by mass percentage: SiO2 25%~35%; Al2O3 12%~19%; Fe2O3 0.1%~0.5%; TiO2 1%~2%; CaO 35%~45%; MgO 6%~12%; K2O 0.1%~0.5%; Na2O 0.1%~0.5%; and loss on ignition 0.5%~2%. For example, the chemical composition of the ore powder in each embodiment and comparative example includes, by mass percentage: SiO2 32.86%; Al2O3 16.24%; Fe2O3 0.38%; TiO2 1.10%; CaO 38.67%; MgO 9.27%; K2O 0.27%; Na2O 0.35%; and loss on ignition 0.86%.

[0045] Weigh and ball-mill the raw materials according to the proportion of the outer layer ceramic until the median particle size of the ceramic powder reaches 8~12 μm, and then remove iron to obtain the outer layer ceramic slurry.

[0046] It is worth noting that the outer body layer of this invention is a calcium-magnesium ceramic, with a crystalline phase content exceeding 90 wt% after firing, primarily composed of anorthite and diopside. By utilizing the difference in phase composition between the inner and outer body layers, the thermal expansion coefficients of the inner and outer body layers can be controlled (the thermal expansion coefficients of anorthite and diopside are lower than those of quartz and silicate glass), resulting in a lower thermal expansion coefficient for the outer body layer compared to the inner body layer. This mismatch in thermal expansion coefficients between the outer-inner-outer body layers allows for the introduction of residual compressive stress on the surface of the building ceramic. Therefore, the outer body layer ceramic is a calcium-magnesium ceramic, with a crystalline phase containing anorthite and diopside as the main phase after firing, and an amorphous glass phase as the auxiliary phase. In optional embodiments, the amorphous phase content of the outer body layer ceramic is ≤12%, the anorthite mass content is 35%~45%, and the diopside mass content is 45%~55%.

[0047] The introduction of tricalcium phosphate can promote phase separation of the high-temperature melt of the outer layer ceramic, and then use the phase separation interface to provide nucleation sites, effectively improving the amorphous crystallization ability of the high-temperature melt of the outer layer ceramic and promoting the precipitation of calcium feldspar and diopside crystalline phases.

[0048] It is worth noting that the application of the outer blank layer can be achieved not only by spray glazing, but also by glazing by dripping and dry application, all of which fall within the scope of protection of this invention.

[0049] It is worth noting that during the ball milling process, the inner and outer layer ceramic slurries also need to be diluted with a diluent (a conventional process in the field of building ceramics preparation) and water. The diluent includes, but is not limited to, any one of water glass, sodium humate, sodium polyacrylate, and sodium tripolyphosphate, and its dosage can be 0.5% to 1.0% of the ceramic raw materials (mineral raw materials) (by mass percentage).

[0050] The outer ceramic slurry should be applied symmetrically to both sides of the inner ceramic body. The specific gravity of the outer ceramic slurry should be 1.55 ~ 1.70 g / cm³. 3 The amount of ceramic slurry applied to the outer layer of the single-sided green body is 800 ~ 1800 g / m². 2 If the applied amount is too low, the residual compressive stress on the surface of the tempered building ceramic (outer blank layer surface) will be too high, while the residual tensile stress at the interface between the inner and outer blank layers will be too high. This will make it easy for the tempered building ceramic to fail under bending stress first at the outer blank-inner blank section, resulting in a poor prestressing strengthening effect, i.e., a low bending strength improvement rate. If the applied amount is too high, the residual compressive stress on the surface of the tempered building ceramic (outer blank layer surface) will be too low, resulting in a poor prestressing strengthening effect, which is not conducive to effectively improving the bending strength of the building ceramic.

[0051] It is worth noting that the present invention applies the outer ceramic slurry symmetrically to both sides of the inner ceramic body, mainly to introduce symmetrical residual stress on the surface of the inner ceramic body, thereby reducing the difficulty of controlling the shape of tempered building ceramic tiles. If the outer ceramic body is applied to only one side of the inner ceramic body (the outer ceramic body and the surface glaze and protective glaze are placed on the two sides of the inner ceramic body respectively), the shape of the tempered building ceramic tile needs to be controlled by the thermal expansion coefficients of the surface glaze, protective glaze, inner ceramic body, and outer ceramic body, which makes it difficult to control the shape of unilateral asymmetric tempered building ceramic tiles. In addition, in order to ensure the shape of unilateral asymmetric tempered building ceramic tiles, the amount of outer ceramic slurry applied is low (the thickness of the outer ceramic body is low), resulting in limited prestressing strengthening effect and a low rate of improvement in the bending strength of tempered building ceramic tiles. For double-sided symmetrical tempered building ceramics (with outer layer ceramic slurry applied symmetrically on both sides of the inner layer ceramic body), the brick shape control method is the same as that of conventional building ceramic products. It is mainly controlled by the cooling rate of the brick surface and the bottom of the brick during the cooling process. The brick shape control is relatively easy, and the amount of outer layer ceramic slurry applied can be increased to enhance its prestressing strengthening effect.

[0052] In an optional embodiment, the porosity of the outer ceramic layer is higher than that of the inner ceramic layer. For example, the porosity of the inner ceramic layer is 3% to 5%, while that of the outer ceramic layer is 15% to 20%.

[0053] After drying, a surface glaze is applied to the outer surface of one side of the blank.

[0054] This invention does not limit the chemical composition of the glaze. Preferably, the chemical composition of the glaze includes, by mass percentage: SiO2 53%~60%; Al2O3 25%~30%; Fe2O3 0.2%~0.5%; TiO2 0.1%~0.2%; CaO 0.2%~0.8%; MgO 0.1%~0.5%; K2O 2%~6%; Na2O 2%~3.5%; ZrO2 4%~8%; and loss on ignition 2%~5%.

[0055] It is worth noting that the surface glaze is a conventional surface glaze for architectural ceramics, primarily serving to cover the body, enhance the whiteness of the brick, and provide ventilation channels during the high-temperature firing process, thus preventing glaze defects. The surface glaze can be applied by spraying or pouring. Preferably, the specific gravity of the surface glaze is 1.40 ~ 1.45 g / cm³. 3 The glaze application rate is 500 ~ 650 g / m². 2 .

[0056] After drying again, inkjet printing of patterns and application of protective glaze are performed sequentially on the surface of the glaze.

[0057] Protective glazes are commonly used in the field of architectural ceramics. This invention does not limit its chemical composition. Preferably, the chemical composition of the protective glaze includes, by mass percentage: SiO2 43%~48%; Al2O3 15%~19%; Fe2O3 0~0.2%; TiO2 0~0.2%; CaO 5%~12%; MgO 3.3%~4.5%; K2O 0.8%~2.7%; Na2O 3.3%~4.6%; ZnO 1.1%~3.8%; BaO 0.6%~7.8%; SrO 0~2%; and loss on ignition 9%~11%. Further preferred, the chemical composition of the protective glaze includes, by mass percentage: SiO2 43%~48%; Al2O3 15%~19%; Fe2O3 0.01%~0.2%; TiO2 0.01%~0.2%; CaO 5%~12%; MgO 3.3%~4.5%; K2O 0.8%~2.7%; Na2O 3.3%~4.6%; ZnO 1.1%~3.8%; BaO 0.6%~7.8%; SrO 0~2%; and loss on ignition 9%~11%. The protective glaze can be applied by spraying or pouring. Preferably, the specific gravity of the protective glaze is 1.30~1.45 g / cm³. 3 The glaze application rate is 400 ~ 800 g / m². 2 .

[0058] It is worth noting that the protective glaze of the present invention is a physical barrier layer (waterproof and seepage-proof), a decorative layer (gloss and stone-like effect), and a functional layer (wear-resistant, anti-slip, etc.) for building ceramics, and its chemical composition can be adjusted and optimized according to the usage scenarios of tempered building ceramics.

[0059] After drying, a ceramic green body is obtained by combining an outer blank, an inner blank, an outer blank, a surface glaze, and a protective glaze layer. After firing and edge grinding, a tempered building ceramic with dual-mechanism prestress synergistic reinforcement can be obtained.

[0060] In an optional embodiment, the drying is performed by warm air drying at a temperature of 150-250°C for 5-10 minutes.

[0061] It is worth noting that drying is a conventional production process for building ceramics, and this invention does not impose any special limitations on it.

[0062] The firing process is carried out in a roller kiln at high temperature, with a maximum firing temperature of 1130 ~ 1160 ℃ and a high-temperature holding time of 15 ~ 30 min.

[0063] It is worth noting that the inner and outer ceramic layers can be fired together. If the firing temperature is too low, the tempered building ceramics will be underfired, resulting in excessive water absorption (>0.5%) and reduced flexural strength. If the firing temperature is too high, the tempered building ceramics will be overfired, resulting in increased porosity and reduced flexural strength.

[0064] This invention primarily utilizes the synergistic effect of the quartz phase transformation in the inner green layer and the thermal mismatch between the inner and outer green layers to introduce residual compressive stress on the surface of the ceramic, achieving a dual-mechanism prestressing synergistic strengthening effect and effectively improving the flexural strength of the tempered building ceramic. Through the chemical composition design of the inner and outer green layers, their phase composition is altered: the inner green layer is a high-silica feldspar ceramic, with its sintered body dominated by an amorphous glass phase and crystalline phases primarily composed of quartz and mullite; the outer green layer is a calcium-magnesium ceramic, with its sintered body dominated by crystalline phases, primarily composed of anorthite and diopside. On the one hand, since the thermal expansion coefficients of anorthite and diopside are lower than those of quartz and amorphous glass phases, the thermal expansion coefficient of the outer ceramic layer is lower than that of the inner ceramic layer. This means that during the cooling process after firing, the shrinkage of the inner ceramic layer is greater than that of the outer ceramic layer. This thermal expansion coefficient mismatch can then be used to introduce residual compressive stress on the surface of the building ceramic. On the other hand, the flux in the inner ceramic layer is mainly K₂O and Na₂O, which avoids the high-temperature melting of SiO₂ by alkaline earth metal oxides, thus forming a residual quartz crystal phase. The phase transformation of the quartz crystal phase during cooling (β-quartz to α-quartz), accompanied by volume shrinkage, can introduce residual compressive stress on the surface of the building ceramic. Therefore, by utilizing the thermal expansion coefficient mismatch and quartz phase transformation shrinkage, the prestressing enhancement effect of building ceramics can be strengthened, and the flexural strength of building ceramics can be significantly improved.

[0065] The method for preparing tempered building ceramics based on dual-mechanism prestressed synergistic reinforcement provided by this invention has the following beneficial effects: (1) The synergistic prestressing effect of the quartz phase transformation of the inner blank layer and the thermal mismatch between the inner and outer blank layers can effectively improve the bending strength of building ceramics.

[0066] (2) The setting of calcium-magnesium outer ceramic layer can not only reduce the manufacturing cost of tempered building ceramics, but also improve the machinability of building ceramics by utilizing its lightweight and high strength characteristics and the inhibitory effect of high porosity on crack propagation.

[0067] (3) By using the structure of outer blank layer-inner blank layer-outer blank layer-glaze-protective glaze layer, that is, the outer blank layer is evenly set on both sides of the inner blank layer, which is not only conducive to the realization of the prestress strengthening effect of building ceramics, but also can significantly improve the brick shape of tempered building ceramics and increase the yield rate.

[0068] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values ​​in the examples below.

[0069] Example 1

[0070] A method for preparing tempered building ceramics based on dual-mechanism prestressed synergistic reinforcement mainly includes the following steps: Step 1. Weigh 35 parts by mass of sodium feldspar, 23 parts by mass of potassium feldspar, 10 parts by mass of ball clay, 5 parts by mass of bentonite, 2 parts by mass of calcined talc, 25 parts by mass of quartz (particle size 325-400 mesh), 0.5 parts by mass of water glass, and 50 parts by mass of water. Add them to a ball mill jar and ball mill until the median particle size of the ceramic powder reaches 8 μm. Then, remove iron and spray granulate to obtain the inner green layer ceramic powder, whose chemical composition includes, by mass percentage: SiO2 76.01%; Al2O3 14.40%; Fe2O3 0.38%; TiO2 0.08%; CaO 0.23%; MgO 0.73%; K2O 2.12%; Na2O 3.22%; loss on ignition 2.83%. Furthermore, a ceramic green body with an inner layer (thickness of 9.0 mm) was prepared by dry pressing and then dried to control the moisture content of the dried ceramic green body to be 0.3%.

[0071] Step 2. Weigh 10 parts by weight of sodium feldspar, 10 parts by weight of potassium feldspar, 10 parts by weight of clay, 5 parts by weight of bentonite, 20 parts by weight of diopside, 40 parts by weight of mineral powder, 5 parts by weight of tricalcium phosphate, 1 part by weight of sodium polyacrylate, and 45 parts by weight of water. Add them to a ball mill jar and ball mill until the median particle size of the ceramic powder reaches 8 μm. Then, remove iron to obtain an outer layer ceramic slurry, and adjust its specific gravity to 1.6 g / cm³ by controlling the moisture content. 3 The chemical composition of the outer ceramic body includes, by mass percentage: SiO2 45.38%; Al2O3 14.26%; Fe2O3 0.49%; TiO2 0.49%; CaO 23.12%; MgO 7.59%; K2O 1.19%; Na2O 1.23%; P2O5 2.09%; and loss on ignition 4.16%.

[0072] Step 3. Apply the outer layer ceramic slurry to the surface of the inner layer ceramic green body using a spray glazing process, with a glaze application rate of 1000 g / m². 2The ceramic green body is then dried. After drying, the outer and inner layers of the ceramic green body are flipped using a flipping machine (with the inner layer surface facing upwards). The outer layer ceramic slurry is then applied to the surface of the inner layer ceramic green body using a spray glazing process, with a glaze application rate of 1000 g / m². 2 And then dry it.

[0073] Step 4. Apply a surface glaze to the dried outer-inner-outer-body ceramic green body using a spray glazing process. The chemical composition of the surface glaze includes, by mass percentage: SiO2 58.30%; Al2O3 25.20%; Fe2O3 0.26%; TiO2 0.10%; CaO 0.27%; MgO 0.10%; K2O 4.66%; Na2O 2.29%; ZrO2 5.16%; loss on ignition 3.66%. The specific gravity of the surface glaze is controlled at 1.4 g / cm³. 3 Glazing amount is 650 g / m 2 .

[0074] Step 5. After drying, inkjet print a pattern onto the surface of the glaze, and then apply a protective glaze using a spray glazing process. The protective glaze is a commonly used antique-style glaze in architectural ceramics, and its chemical composition includes, by mass percentage: SiO2 47.10%; Al2O3 18.00%; Fe2O3 0.20%; TiO2 0.15%; CaO 5.81%; MgO 3.80%; K2O 2.64%; Na2O 3.34%; ZnO 1.55%; BaO 7.27%; loss on ignition 10.14%. The specific gravity of the protective glaze is 1.3 g / cm³. 3 Glazing amount is 800 g / m 2 .

[0075] Step 6. After drying, place the ceramic green body consisting of outer green body layer-inner green body layer-outer green body layer-glaze-protective glaze layer into a ceramic roller kiln for high-temperature firing. The firing process parameters are: maximum firing temperature of 1130 ℃ and high-temperature holding time of 15 min.

[0076] Step 7. After edge grinding, tempered building ceramics with dual-mechanism prestress synergistic reinforcement can be obtained.

[0077] The tempered building ceramics prepared in Example 1 were cut and processed. According to GB / T 3810.4-2016 "Test Methods for Ceramic Tiles - Part 4: Determination of Modulus of Fracture and Breaking Strength", the flexural strength (modulus of fracture) of the tempered building ceramics was measured to be 114.45±7.62 MPa.

[0078] The phase composition of the inner and outer green layers in tempered building ceramics was determined by XRD, as shown below. Figure 2 , Figure 3As shown in Table 1, the content of each phase in the ceramic sample was obtained by semi-quantitative calculation of the XRD patterns using TOPAS software. The XRD pattern of the inner body layer shows obvious amorphous "bun peaks," indicating the presence of a large amount of amorphous phase (its phase composition is dominated by amorphous phases), with quartz and mullite as the main crystalline phases, and only a small amount of corundum crystalline phase. The outer body layer ceramic has a crystalline phase content as high as 90.77 wt%, mainly diopside and anorthite, with only a small amount of quartz.

[0079] Table 1. Semi-quantitative calculation results of the phase composition content in the inner and outer green layers of ceramics.

[0080] Furthermore, the coefficients of thermal expansion of the inner and outer ceramic layers were measured using a coefficient of thermal expansion measuring instrument, such as... Figure 4 As shown, the coefficient of thermal expansion of the inner layer (the coefficient of thermal expansion in the range of room temperature to 600 ℃ is 8.11 × 10⁻⁶) is... -6 K -1 The coefficient of thermal expansion of the outer ceramic layer is greater than that of the outer ceramic layer (7.03×10⁻⁶ in the range of room temperature to 600 ℃). -6 K -1 Furthermore, the thermal expansion coefficient curve of the inner ceramic layer sample exhibits a "peak" near 564 ℃, meaning that the thermal expansion coefficient of the ceramic sample suddenly increases when the temperature reaches 564 ℃. This can amplify the shrinkage difference between the inner and outer ceramic layers during the cooling process, which is beneficial for increasing the residual compressive stress on the surface of the building ceramic. The main reason for the formation of the thermal expansion coefficient "peak" at 564 ℃ is that the inner ceramic layer contains 26.76 wt% quartz crystalline phase. During the heating process, the phase transformation of quartz (α-quartz to β-quartz) leads to volume expansion, which in turn significantly increases the heating expansion rate of the inner ceramic layer. Since this transformation is a displacement transformation, it has reversible characteristics. That is, during the cooling process after firing, the phase transformation of quartz (β-quartz to α-quartz) will lead to volume shrinkage, which is beneficial for introducing residual compressive stress on the surface of the building ceramic.

[0081] Furthermore, the microstructure of the tempered building ceramic interface was measured using SEM, such as... Figure 5As shown, the interfaces between the outer and inner blank layers (lower side of the tempered building ceramic) and between the inner and outer blank layers and the surface glaze (upper side of the tempered building ceramic) are clearly defined and without obvious defects. This indicates that the outer and inner blank layers are well bonded and can be considered ideal interfaces, effectively transferring the residual stress caused by thermal mismatch between the two, thus meeting the requirements for prestressing strengthening. Furthermore, the porosity of the outer blank layer ceramic is significantly higher than that of the inner blank layer. On the one hand, the porosity inhibits crack propagation during machining of the tempered building ceramic, reducing processing stress and making it less prone to sudden damage caused by crack instability during cutting and grinding, effectively improving its machinability. On the other hand, the outer blank layer ceramic possesses a distinct nanocrystalline structure, such as... Figure 6 As shown, the average size of diopside and anorthite grains is approximately 452.5 ± 96.2 nm. Nanocrystals can make the stress distribution during processing more uniform, avoid brittle fracture caused by excessive local stress, and also help improve the machinability of tempered building ceramics.

[0082] Example 2

[0083] A method for preparing tempered building ceramics based on dual-mechanism prestressed synergistic reinforcement mainly includes the following steps: Step 1. Weigh 18 parts by mass of sodium feldspar, 41 parts by mass of potassium feldspar, 30 parts by mass of ball clay, 2 parts by mass of bentonite, 4 parts by mass of calcined talc, 5 parts by mass of quartz (400-600 mesh), 0.8 parts by mass of sodium humate, and 50 parts by mass of water. Add them to a ball mill jar and ball mill until the median particle size of the ceramic powder reaches 12 μm. Then, remove iron and spray granulate to obtain the inner green layer ceramic powder. Its chemical composition includes, by mass percentage: SiO2 66.25%; Al2O3 20.73%; Fe2O3 0.60%; TiO2 0.10%; CaO 0.17%; MgO 1.38%; K2O 3.66%; Na2O 1.85%; loss on ignition 5.26%. Furthermore, a ceramic green body with an inner layer (thickness of 6.0 mm) was prepared by dry pressing and then dried to control the moisture content of the dried ceramic green body to 0.5%.

[0084] Step 2. Weigh 7 parts by weight of sodium feldspar, 14 parts by weight of potassium feldspar, 25 parts by weight of clay, 3 parts by weight of bentonite, 25 parts by weight of diopside, 20 parts by weight of mineral powder, 6 parts by weight of tricalcium phosphate, 1 part by weight of sodium polyacrylate, and 45 parts by weight of water. Add them to a ball mill jar and ball mill until the median particle size of the ceramic powder reaches 12 μm. Then, remove iron to obtain an outer layer ceramic slurry, and adjust its specific gravity to 1.70 g / cm³ by controlling the moisture content. 3The chemical composition of the outer ceramic body includes, by mass percentage: SiO2 48.16%; Al2O3 15.80%; Fe2O3 0.57%; TiO2 0.29%; CaO 17.12%; MgO 6.71%; K2O 1.78%; Na2O 0.99%; P2O5 2.50%; and loss on ignition 6.08%.

[0085] Step 3. Apply the outer layer ceramic slurry to the surface of the inner layer ceramic green body using a spray glazing process, with a glaze application rate of 800 g / m². 2 The ceramic green body is then dried. After drying, the outer and inner layers of the ceramic green body are flipped using a flipping machine (with the inner layer surface facing upwards). The outer layer ceramic slurry is then applied to the surface of the inner layer ceramic green body using a spray glazing process, with a glaze application rate of 800 g / m². 2 And then dry it.

[0086] Step 4. Apply a surface glaze to the dried outer-inner-outer-body ceramic green body using a spray glazing process. The chemical composition of the surface glaze includes, by mass percentage: SiO2 58.30%; Al2O3 25.20%; Fe2O3 0.26%; TiO2 0.10%; CaO 0.27%; MgO 0.10%; K2O 4.66%; Na2O 2.29%; ZrO2 5.16%; loss on ignition 3.66%. The specific gravity of the surface glaze is controlled at 1.45 g / cm³. 3 Glazing amount is 500 g / m 2 .

[0087] Step 5. After drying, inkjet print patterns are sequentially applied to the surface of the glaze. A protective glaze is then applied using a spray glazing process. The protective glaze is a commonly used antique-style glaze in architectural ceramics, and its chemical composition, by mass percentage, is: SiO2 47.10%; Al2O3 18.00%; Fe2O3 0.20%; TiO2 0.15%; CaO 5.81%; MgO 3.80%; K2O 2.64%; Na2O 3.34%; ZnO 1.55%; BaO 7.27%; loss on ignition 10.14%. The specific gravity of the protective glaze is 1.45 g / cm³. 3 Glazing amount is 400 g / m 2 .

[0088] Step 6. After drying, place the ceramic green body consisting of outer green body layer-inner green body layer-outer green body layer-glaze-protective glaze layer into a ceramic roller kiln for high-temperature firing. The firing process parameters are: maximum firing temperature of 1160 ℃ and high-temperature holding time of 15 min.

[0089] Step 7. After edge grinding, tempered building ceramics with dual-mechanism prestress synergistic reinforcement can be obtained.

[0090] The tempered building ceramics prepared in Example 2 were cut and processed. According to GB / T 3810.4-2016 "Test Methods for Ceramic Tiles - Part 4: Determination of Modulus of Fracture and Breaking Strength", the flexural strength (modulus of rupture) of the tempered building ceramics was measured to be 109.32±8.15 MPa.

[0091] Example 3

[0092] A method for preparing tempered building ceramics based on dual-mechanism prestressed synergistic reinforcement mainly includes the following steps: Step 1. Weigh 25 parts by mass of sodium feldspar, 30 parts by mass of potassium feldspar, 20 parts by mass of clay, 3 parts by mass of bentonite, 6 parts by mass of calcined talc, 16 parts by mass of quartz (400-500 mesh), 0.6 parts by mass of sodium tripolyphosphate, and 48 parts by mass of water. Add them to a ball mill jar and ball mill until the median particle size of the ceramic powder reaches 10 μm. Then, remove iron and spray granulate to obtain the inner green layer ceramic powder. Its chemical composition includes, by mass percentage: SiO2 71.21%; Al2O3 16.95%; Fe2O3 0.48%; TiO2 0.09%; CaO 0.22%; MgO 1.97%; K2O 2.77%; Na2O 2.40%; loss on ignition 3.91%. Furthermore, a ceramic green body with an inner layer (thickness of 9.0 mm) was prepared by dry pressing and then dried to control the moisture content of the dried ceramic green body to be 0.3%~0.5%.

[0093] Step 2. Weigh out 4 parts by weight of sodium feldspar, 20 parts by weight of potassium feldspar, 17 parts by weight of clay, 2 parts by weight of bentonite, 35 parts by weight of diopside, 20 parts by weight of mineral powder, 2 parts by weight of tricalcium phosphate, 0.8 parts by weight of water glass, and 50 parts by weight of water. Add them to a ball mill jar and ball mill until the median particle size of the ceramic powder reaches 10 μm. Then, remove iron to obtain an outer layer ceramic slurry, and adjust its specific gravity to 1.55 g / cm³ by controlling the moisture content. 3 The chemical composition of the outer ceramic body includes, by mass percentage: SiO2 49.77%; Al2O3 13.82%; Fe2O3 0.59%; TiO2 0.29%; CaO 17.34%; MgO 8.58%; K2O 1.90%; Na2O 0.69%; P2O5 0.83%; and loss on ignition 6.19%.

[0094] Step 3. Apply the outer layer ceramic slurry to the surface of the inner layer ceramic green body using a spray glazing process, with a glaze application rate of 1000 g / m². 2The ceramic green body is then dried. After drying, the outer and inner layers of the ceramic green body are flipped using a flipping machine (with the inner layer surface facing upwards). The outer layer ceramic slurry is then applied to the surface of the inner layer ceramic green body using a spray glazing process, with a glaze application rate of 1800 g / m². 2 And then dry it.

[0095] Step 4. Apply a surface glaze to the dried outer-inner-outer-body ceramic green body using a spray glazing process. The chemical composition of the surface glaze includes, by mass percentage: SiO2 58.30%; Al2O3 25.20%; Fe2O3 0.26%; TiO2 0.10%; CaO 0.27%; MgO 0.10%; K2O 4.66%; Na2O 2.29%; ZrO2 5.16%; loss on ignition 3.66%. The specific gravity of the surface glaze is controlled at 1.40 g / cm³. 3 Glazing amount is 550 g / m 2 .

[0096] Step 5. After drying, inkjet print patterns are sequentially applied to the surface of the glaze. A protective glaze is then applied using a spray glazing process. The protective glaze is a commonly used antique-style glaze in architectural ceramics, and its chemical composition includes, by mass percentage: SiO2 47.10%; Al2O3 18.00%; Fe2O3 0.20%; TiO2 0.15%; CaO 5.81%; MgO 3.80%; K2O 2.64%; Na2O 3.34%; ZnO 1.55%; BaO 7.27%; loss on ignition 10.14%. The specific gravity of the protective glaze is 1.40 g / cm³. 3 Glazing amount is 600 g / m 2 .

[0097] Step 6. After drying, place the ceramic green body consisting of outer green body layer-inner green body layer-outer green body layer-glaze-protective glaze layer into a ceramic roller kiln for high-temperature firing. The firing process parameters are: maximum firing temperature of 1150 ℃ and high-temperature holding time of 20 min.

[0098] Step 7. After edge grinding, tempered building ceramics with dual-mechanism prestress synergistic reinforcement can be obtained.

[0099] The tempered building ceramics prepared in Example 1 were cut and processed. According to GB / T 3810.4-2016 "Test Methods for Ceramic Tiles - Part 4: Determination of Modulus of Fracture and Breaking Strength", the flexural strength (modulus of fracture) of the tempered building ceramics was measured to be 121.69±9.58 MPa.

[0100] Comparative Example 1 The main preparation process of Comparative Example 1 is basically the same as that of Example 1. The main difference is that Comparative Example 1 consists only of inner body layer-surface glaze-protective glaze, and the raw material composition and preparation process of its inner body layer are exactly the same as those of Example 1.

[0101] Step 1. Weigh 35 parts by mass of sodium feldspar, 23 parts by mass of potassium feldspar, 10 parts by mass of ball clay, 5 parts by mass of bentonite, 2 parts by mass of calcined talc, 25 parts by mass of quartz (particle size 325-400 mesh), 0.5 parts by mass of water glass, and 50 parts by mass of water. Add them to a ball mill jar and ball mill until the median particle size of the ceramic powder reaches 8 μm. Then, remove iron and spray granulate to obtain the inner green layer ceramic powder, whose chemical composition includes, by mass percentage: SiO2 76.01%; Al2O3 14.40%; Fe2O3 0.38%; TiO2 0.08%; CaO 0.23%; MgO 0.73%; K2O 2.12%; Na2O 3.22%; loss on ignition 2.83%. Furthermore, a ceramic green body with an inner layer (thickness of 9.0 mm) was prepared by dry pressing and then dried to control the moisture content of the dried ceramic green body to be 0.3%.

[0102] Step 2. Apply a top glaze to the dried inner layer of the ceramic green body using a spray glazing process. The chemical composition of the top glaze includes, by mass percentage: SiO2 58.30%; Al2O3 25.20%; Fe2O3 0.26%; TiO2 0.10%; CaO 0.27%; MgO 0.10%; K2O 4.66%; Na2O 2.29%; ZrO2 5.16%; loss on ignition 3.66%. The specific gravity of the top glaze is controlled at 1.40 g / cm³. 3 Glazing amount is 650 g / m 2 .

[0103] Step 3. After drying, inkjet-printed patterns are sequentially applied to the surface of the glaze. A protective glaze is then applied using a spray glazing process. The protective glaze is a commonly used antique-style glaze in architectural ceramics, and its chemical composition includes, by mass percentage: SiO2 47.10%; Al2O3 18.00%; Fe2O3 0.20%; TiO2 0.15%; CaO 5.81%; MgO 3.80%; K2O 2.64%; Na2O 3.34%; ZnO 1.55%; BaO 7.27%; loss on ignition 10.14%. The specific gravity of the protective glaze is 1.30 g / cm³. 3 Glazing amount is 800 g / m 2 .

[0104] Step 4. After drying, place the ceramic green body with inner body layer-surface glaze-protective glaze layer in a ceramic roller kiln for high-temperature firing. The firing process parameters are: maximum firing temperature of 1130 ℃ and high-temperature holding time of 15 min.

[0105] Step 5. After edge grinding, the inner layer of building ceramics can be obtained. Further, the building ceramics obtained in Comparative Example 1 are cut and processed. According to GB / T 3810.4-2016 "Test Methods for Ceramic Tiles Part 4: Determination of Modulus of Rupture and Breaking Strength", the flexural strength (modulus of rupture) of the inner layer of building ceramics is measured to be 50.35±5.02 MPa, meaning that after tempering treatment, the flexural strength of the building ceramics is increased by 1.27 times.

[0106] Comparative Example 2 The ceramic body prepared in Comparative Example 2 is the outer ceramic body of Example 1, and its specific preparation process is as follows: Step 1. Weigh 10 parts by weight of sodium feldspar, 10 parts by weight of potassium feldspar, 10 parts by weight of clay, 5 parts by weight of bentonite, 20 parts by weight of diopside, 40 parts by weight of mineral powder, 5 parts by weight of tricalcium phosphate, 1.0 part by weight of sodium polyacrylate, and 45 parts by weight of water. Add them to a ball mill jar and ball mill until the median particle size of the ceramic powder reaches 8 μm. Then, remove iron and spray granulate to obtain the outer layer ceramic powder, whose chemical composition includes, by mass percentage: SiO2 45.38%; Al2O3 14.26%; Fe2O3 0.49%; TiO2 0.49%; CaO 23.12%; MgO 7.59%; K2O 1.19%; Na2O 1.23%; P2O5 2.09%; loss on ignition 4.16%. Furthermore, a ceramic green body with an outer layer (9.0 mm thick) was prepared by dry pressing and then dried to control the moisture content of the dried ceramic green body to be 0.3%.

[0107] Step 2. Apply a top glaze to the dried outer ceramic green body using a spray glazing process. The chemical composition of the top glaze includes, by mass percentage: SiO2 58.30%; Al2O3 25.20%; Fe2O3 0.26%; TiO2 0.10%; CaO 0.27%; MgO 0.10%; K2O 4.66%; Na2O 2.29%; ZrO2 5.16%; loss on ignition 3.66%. The specific gravity of the top glaze is controlled at 1.40 g / cm³. 3 Glazing amount is 650 g / m 2 .

[0108] Step 3. After drying, inkjet-printed patterns are sequentially applied to the surface of the glaze. A protective glaze is then applied using a spray glazing process. The protective glaze is a commonly used antique-style glaze in architectural ceramics, and its chemical composition includes, by mass percentage: SiO2 47.10%; Al2O3 18.00%; Fe2O3 0.20%; TiO2 0.15%; CaO 5.81%; MgO 3.80%; K2O 2.64%; Na2O 3.34%; ZnO 1.55%; BaO 7.27%; loss on ignition 10.14%. The specific gravity of the protective glaze is 1.30 g / cm³. 3 Glazing amount is 800 g / m 2 .

[0109] Step 4. After drying, place the ceramic green body with outer body layer-glaze layer-protective glaze layer in a ceramic roller kiln for high-temperature firing. The firing process parameters are: maximum firing temperature of 1130 ℃ and high-temperature holding time of 15 min.

[0110] Step 5. After edge grinding, the outer layer of building ceramic is obtained. Further, the building ceramic obtained in Comparative Example 2 is cut and processed. According to GB / T 3810.4-2016 "Test Methods for Ceramic Tiles Part 4: Determination of Modulus of Rupture and Breaking Strength", the flexural strength (modulus of rupture) of the tempered building ceramic is measured to be 78.26 ± 5.71 MPa. The flexural strength of the tempered building ceramic obtained in Example 1 is 46% higher than that of Comparative Example 2 (outer layer ceramic), indicating that the flexural strength of the tempered building ceramic is higher than the intrinsic strength of the outer layer ceramic. The increase in flexural strength is the effect of the residual compressive stress on the surface of the tempered building ceramic.

[0111] In addition, indentation tests were conducted on the outer blank layer in Example 1 and the outer blank layer in Comparative Example 2 using a Vickers hardness tester (indentation load was 5 kgf, holding time was 10 s), and the indentation morphology is as follows. Figure 7 As shown, the indentation size of the outer blank layer in Comparative Example 2 is significantly larger than that of the outer blank layer in Example 1. Moreover, there are obvious crack propagation and local damage at the edge of the indentation in Comparative Example 2, while the edge of the indentation in Example 1 is clear, with no obvious crack initiation, propagation, or local damage. This proves that the outer blank layer in Example 1 bears significant residual compressive stress. Under the action of residual compressive stress, the ceramic outer blank layer has enhanced resistance to indenter intrusion, thereby reducing the indentation size and the size of defects such as cracks and chipping at the indentation.

[0112] Comparative Example 3 Comparative Example 3 is basically the same as Example 1 in terms of technical solution, the main difference being that: in Comparative Example 3, the outer ceramic layer (calcium-magnesium ceramic) is replaced with high-alumina feldspar ceramic (whose coefficient of thermal expansion in the range of room temperature to 600 ℃ is 7.62×10). -6 K-1 (Lower than the inner blank layer in Example 1).

[0113] Step 1. Weigh 35 parts by mass of sodium feldspar, 23 parts by mass of potassium feldspar, 10 parts by mass of ball clay, 5 parts by mass of bentonite, 2 parts by mass of calcined talc, 25 parts by mass of quartz (particle size 325-400 mesh), 0.5 parts by mass of water glass, and 50 parts by mass of water. Add them to a ball mill jar and ball mill until the median particle size of the ceramic powder reaches 8 μm. Then, remove iron and spray granulate to obtain the inner green layer ceramic powder, whose chemical composition includes, by mass percentage: SiO2 76.01%; Al2O3 14.40%; Fe2O3 0.38%; TiO2 0.08%; CaO 0.23%; MgO 0.73%; K2O 2.12%; Na2O 3.22%; loss on ignition 2.83%. Furthermore, a ceramic green body with an inner layer (thickness of 9.0 mm) was prepared by dry pressing and then dried to control the moisture content of the dried ceramic green body to be 0.3%.

[0114] Step 2. Weigh 40 parts by weight of sodium feldspar, 20 parts by weight of potassium feldspar, 35 parts by weight of clay, 5 parts by weight of calcined talc, 1.0 part by weight of sodium polyacrylate, and 50 parts by weight of water. Add them to a ball mill jar and ball mill until the median particle size of the ceramic powder reaches 8 μm. Then, remove iron to obtain an outer layer ceramic slurry, and adjust its specific gravity to 1.60 g / cm³ by controlling the moisture content. 3 The chemical composition of the outer ceramic body includes, by mass percentage: SiO2 64.47%; Al2O3 21.68%; Fe2O3 0.51%; TiO2 0.11%; CaO 0.25%; MgO 1.67%; K2O 2.65%; Na2O 3.69%; and loss on ignition 4.97%.

[0115] Step 3. Apply the outer layer ceramic slurry to the surface of the inner layer ceramic green body using a spray glazing process, with a glaze application rate of 1000 g / m². 2 The ceramic green body is then dried. After drying, the outer and inner layers of the ceramic green body are flipped using a flipping machine (with the inner layer surface facing upwards). The outer layer ceramic slurry is then applied to the surface of the inner layer ceramic green body using a spray glazing process, with a glaze application rate of 1000 g / m². 2 And then dry it.

[0116] Step 4. Apply a surface glaze to the dried outer-inner-outer-body ceramic green body using a spray glazing process. The chemical composition of the surface glaze includes, by mass percentage: SiO2 58.30%; Al2O3 25.20%; Fe2O3 0.26%; TiO2 0.10%; CaO 0.27%; MgO 0.10%; K2O 4.66%; Na2O 2.29%; ZrO2 5.16%; loss on ignition 3.66%. The specific gravity of the surface glaze is controlled at 1.40 g / cm³. 3 Glazing amount is 650 g / m 2 .

[0117] Step 5. After drying, inkjet print patterns are sequentially applied to the surface of the glaze. A protective glaze is then applied using a spray glazing process. The protective glaze is a commonly used antique-style glaze in architectural ceramics, and its chemical composition includes, by mass percentage: SiO2 47.10%; Al2O3 18.00%; Fe2O3 0.20%; TiO2 0.15%; CaO 5.81%; MgO 3.80%; K2O 2.64%; Na2O 3.34%; ZnO 1.55%; BaO 7.27%; loss on ignition 10.14%. The specific gravity of the protective glaze is 1.30 g / cm³. 3 Glazing amount is 800 g / m 2 .

[0118] Step 6. After drying, place the ceramic green body consisting of outer green body layer-inner green body layer-outer green body layer-glaze-protective glaze layer into a ceramic roller kiln for high-temperature firing. The firing process parameters are: maximum firing temperature of 1130 ℃ and high-temperature holding time of 15 min.

[0119] Step 7. After edge grinding, conventional tempered building ceramics can be obtained. Further, the tempered building ceramics obtained in Comparative Example 3 were cut and processed. According to GB / T 3810.4-2016 "Test Methods for Ceramic Tiles Part 4: Determination of Modulus of Fracture and Breaking Strength", the flexural strength (modulus of rupture) of the tempered building ceramics was measured to be 67.58±5.39 MPa, which is only 34% higher than that of the inner layer ceramic (Comparative Example 1). That is, the increase in flexural strength of the conventional tempered building ceramics (34%) is significantly lower than that of the tempered building ceramics with dual-mechanism synergistic strengthening (Example 1, with an increase as high as 127%).

Claims

1. A method for preparing tempered building ceramics based on dual-mechanism prestressed synergistic reinforcement, characterized in that, The preparation method includes the following steps: Step 1: Prepare the inner layer ceramic powder into an inner layer ceramic body; the chemical composition of the inner layer ceramic includes, by mass percentage: SiO2 66%~78%; Al2O3 14%~21%; Fe2O3 0.3%~0.6%; TiO2 0~0.1%; CaO 0.1%~0.3%; MgO 0.7%~2.0%; K2O 2.0%~3.7%; Na2O 1.8%~3.5%; loss on ignition 2%~6%; the inner layer ceramic is a high-silica feldspar ceramic, and its phase after firing is mainly amorphous glass phase, with crystalline phases containing quartz and mullite as auxiliary phases; Step 2: Apply outer layer ceramic slurry to both the surface and bottom of the inner layer ceramic body to form an outer-inner-outer layer composite ceramic body. The chemical composition of the outer layer ceramic includes, by mass percentage: SiO2 45%~50%; Al2O3 13%~16%; Fe2O3 0.3%~0.6%; TiO2 0~0.5%; CaO 17%~25%; MgO 6.7%~8.6%; K2O 1.0%~1.9%; Na2O 0.6%~1.5%; P2O5 0.8%~2.5%; loss on ignition 3%~7%. The outer layer ceramic is a calcium-magnesium ceramic, and its post-firing phase is mainly composed of crystalline phases containing anorthite and diopside, with an amorphous glassy phase as the auxiliary phase. The specific gravity of the outer layer ceramic slurry is 1.55~1.70 g / cm³. 3 The application rate of ceramic slurry on one side of the outer layer is 800~1800 g / m. 2 ; Step 3: Apply a surface glaze to the surface of the laminated ceramic body consisting of an outer blank, an inner blank, and an outer blank; Step 4: Print a pattern using ordinary ink on the surface of the laminated ceramic body (outer blank-inner blank-outer blank) after applying the surface glaze. Step 5: Apply a protective glaze to the surface of the laminated ceramic body consisting of an outer blank, an inner blank, and an outer blank after inkjet printing of a pattern using ordinary ink. Step 6: Fire the laminated ceramic body with outer blank-inner blank-outer blank after applying protective glaze to obtain tempered building ceramics based on dual-mechanism prestress synergistic strengthening.

2. The preparation method according to claim 1, characterized in that, The mineral composition of the inner ceramic body includes, by mass percentage: 18%~35% sodium feldspar; 23%~41% potassium feldspar; 10%~30% clay; 2%~5% bentonite; 2%~6% calcined talc; and 5%~25% quartz.

3. The preparation method according to claim 1, characterized in that, The mineral composition of the outer ceramic body includes, by mass percentage: 4%~10% sodium feldspar; 10%~20% potassium feldspar; 10%~25% clay; 2%~5% bentonite; 20%~35% diopside; 20%~40% mineral powder; and 2%~6% tricalcium phosphate.

4. The preparation method according to claim 1, characterized in that, The coefficient of thermal expansion of the inner ceramic layer is greater than that of the outer ceramic layer; the coefficient of thermal expansion of the inner ceramic layer is 7.8 × 10⁻⁶ ℃ in the range of room temperature to 600 ℃. -6 ~9.0×10 -6 K -1 The coefficient of thermal expansion of the outer ceramic layer is 6.5 × 10⁻⁶ in the range of room temperature to 600 °C. -6 ~7.2×10 -6 K -1 .

5. The preparation method according to claim 1, characterized in that, The crystalline phase of the outer layer ceramic has a nanocrystalline structure, and the porosity of the outer layer ceramic is higher than that of the inner layer ceramic.

6. The preparation method according to claim 1, characterized in that, The chemical composition of the glaze includes, by mass percentage: SiO2 53%~60%; Al2O3 25%~30%; Fe2O3 0.2%~0.5%; TiO2 0.1%~0.2%; CaO 0.2%~0.8%; MgO 0.1%~0.5%; K2O 2%~6%; Na2O 2%~3.5%; ZrO2 4%~8%; and loss on ignition 2%~5%.

7. The preparation method according to claim 1, characterized in that, The glaze is applied by spraying or pouring; the specific gravity of the glaze is 1.40~1.45 g / cm³. 3 The glaze application rate is 500~650 g / m². 2 .

8. The preparation method according to claim 1, characterized in that, The chemical composition of the protective glaze includes, by mass percentage: SiO2 43%~48%; Al2O3 15%~19%; Fe2O3 0%~0.2%; TiO2 0%~0.2%; CaO 5%~12%; MgO 3.3%~4.5%; K2O 0.8%~2.7%; Na2O 3.3%~4.6%; ZnO 1.1%~3.8%; BaO 0.6%~7.8%; SrO 0%~2%; and loss on ignition 9%~11%.

9. The preparation method according to claim 1, characterized in that, The protective glaze is applied by spraying or pouring; the specific gravity of the protective glaze is 1.30~1.45 g / cm³. 3 The glaze application rate is 400~800 g / m². 2 .

10. The preparation method according to claim 1, characterized in that, The maximum firing temperature is 1130~1160 ℃, and the high-temperature holding time is 15~30 min.

Citation Information

Patent Citations

  • Coating slurry for enhancing prestress of building ceramic and preparation method and building ceramic product of coating slurry

    CN109336556A

  • A coating slurry for prestressed reinforcement of building ceramics, its preparation method, and building ceramic products thereof.

    CN109336556B

  • Preparation method of high-strength ion exchange pre-stressed albite porcelain and porcelain product thereof

    CN109608181A

  • A method for preparing ion-exchange reinforced prestressed vitrified bricks and its ceramic products

    CN109704721B

  • A gradient-coated prestressed reinforced architectural ceramic product and its preparation method

    CN110723988B